Serotype Is Associated With High Rate of Colistin Resistance Among Clinical Isolates of Salmonella - Luo, Qixia; Wang, Yuan; Fu, Hao; Yu, Xiao; Zheng, Beiwen; Chen, Yunbo; Berglund, Björn; Xiao, Yonghong (Frontiers in Microbiology, 2020)
To investigate the prevalence, probable mechanisms and serotype correlation of colistin resistance in clinical isolates of Salmonella from patients in China, Salmonella isolates were collected from fecal and blood samples of patients. In this study, 42.8% (136/318) clinical isolated Salmonella were resistant to colistin. MIC distribution for colistin at serotype level among the two most prevalent serotypes originating from humans in China indicated that Salmonella Enteritidis (83.9% resistance, 125/149) were significantly less susceptible than Salmonella Typhimurium (15.3% resistance, 9/59, P<0.01). mcr genes and mutations in PmrAB confer little for rate of colistin resistant Salmonella isolated from human patients. Phylogenetic tree based on core-genome single nucleotide polymorphisms (SNPs) was separately by the serotypes and implied a diffused distribution of MICs in the same serotype isolates. Relatvie expression levels of colistin resistant related pmr genes were significantly higher in non-mcr colistin resistant S. Typhimurium than in colistin sensitive S.Typhimurium, but no discernable differences between colistin resistant and sensitive S. Enteritidis, indicating a different mechanism between colistin resistant S. Typhimurium and S. Enteritidis. In conclusion, colistin susceptibility and colistin resistant mechanism of clinical isolated Salmonella were closely associated with specific serotypes, at least in the two most prevelent serotype Enteritidis and Typhimurium. We suggest clinical microbiology laboratory interpreting Salmonella colistin MIC results in the serotype level.